Factors Driving Patient Preferences for Growth Hormone Deficiency (GHD) Injection Regimen and Injection Device Features: A Discrete Choice Experiment - McNamara, Michelle; Turner-Bowker, Diane M; Westhead, Hal; Yaworsky, Andrew; Palladino, Andrew; Gross, Hillary; Pleil, Andreas M; Loftus, Jane (Patient preference and adherence, 2020)
The daily injection burden of recombinant human growth hormone (r-hGH) replacement therapy to treat growth hormone deficiency (GHD) may reduce compliance and limit treatment benefit. Research is needed to evaluate patient preferences for GHD injection regimen and device features. Quantitatively evaluate factors driving preferences for r-hGH injection regimen and device features among pediatric (3-17 years, and caregivers) and adult (≥25 years) patients with GHD using a discrete choice experiment (DCE) approach. The DCE was part of a broader, cross-sectional observational field study to develop clinical outcome assessments (COAs) that assess the experience of patients taking r-hGH injections. Following ethics approval, discrete choice data were collected through an online questionnaire from consented participants recruited from eight sites in the United States. Participants were presented with 20 choice tasks, each comprising different combinations of two profiles. Participants were then shown the same set of three hypothetical device and injection profiles (ie, storage, preparation, injection type device, maintenance, dose setting, injection schedule) and asked whether they would choose each profile over their current device and schedule. Choice-based conjoint analyses were used to estimate the marginal utilities and values for treatment attributes. Subject preferences were estimated at individual and aggregate levels. Two hundred and twenty-four participants completed the DCE (n=75 adults, n=79 adolescent/caregiver dyads, n=70 child/caregiver dyads). Injection schedule was the strongest predictor of choice for the total sample and each patient group. Less frequent injection schedules were more likely to be chosen by participants. A "ready to use" injection was preferred, with no preference for auto-injector versus needle-free device. Most participants would choose the hypothetical injection devices and less frequent dosing over their current daily administered device schedule. Patients prefer a less frequent injection regimen for treating GHD. Addressing patient preferences may improve compliance, adherence, and ultimately, clinical outcomes.